Flow past a moderately heated horizontal cylinder at low Reynolds number. (June 2016) - Ajith Kumar, S; Lal, S Anil; Sameen, A
Flow past a heated two-dimensional cylinder in the laminar regime is investigated. A hybrid finite element–finite volume method is used to solve Navier–Stokes and energy equations. The vortex shedding frequency defined nondimensionally as Strouhal number is observed to be increasing with heating. Vortex shedding behind heated cylinder exhibits asymmetry in wake region due to stable and unstable density stratification below and above the cylinder, respectively. A negative lift is generated due to heating, in an otherwise symmetric zero time-averaged lift configuration, due to skewness in vortex shedding towards the direction of buoyancy. We also note that the heating brings down the drag for the cases considered here. The thermal energy transport due to convection, defined by nondimensional Nusselt number is found to increase only marginally with cylinder heating.